COLLABORATIVE GOVERNANCE DAN URBAN FARMING: PILAR KETAHANAN PANGAN LOKAL DI ERA MODERN KOTA METRO PROVINSI LAMPUNG - Angga Natalia; Wilia Novi Aryani; Tatik Rohmawati (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2026)
Urban farming has emerged as a strategy to address food security challenges in Metro City, Lampung Province. While it has the potential to enhance food availability, empower communities, and support environmental sustainability, previous research has predominantly focused on technical aspects, with limited attention to collaborative governance. This study explores the role of collaborative governance in supporting urban farming to strengthen local food security in small cities. Using a qualitative descriptive approach, data were collected through interviews, observations, and document studies involving key actors such as the Food Security, Agriculture, and Fisheries Agency of Metro City, urban farming communities, and the private sector. The analysis applied the Collaborative Governance framework by Ansell and Gash, focusing on starting conditions, institutional design, facilitative leadership, collaborative processes, and intermediate outcomes. The findings indicate that urban farming in Metro City has received regulatory support, community participation, and contributions from the private sector. However, facilitative leadership emerged as the strongest indicator, with effective conflict mediation mechanisms and strong community involvement. At the same time, institutional design was identified as the weakest, with gaps in product certification and coordination. This study contributes to the theory of Collaborative Governance by demonstrating that, while collaboration among actors in Metro City has resulted in positive social and economic outcomes, long-term sustainability still depends on improving institutional capacity and refining more inclusive institutional designs. This study emphasizes the need to strengthen cross-actor collaboration, facilitate product certification, and provide ongoing support to ensure that urban farming becomes a sustainable pillar of local food security.